2014
DOI: 10.1371/journal.pone.0102420
|View full text |Cite|
|
Sign up to set email alerts
|

The Anti-Diabetic Drug Metformin Reduces BACE1 Protein Level by Interfering with the MID1 Complex

Abstract: Alzheimer’s disease (AD), the most common form of dementia in the elderly, is characterized by two neuropathological hallmarks: senile plaques, which are composed of Aβ peptides, and neurofibrillary tangles, which are composed of hyperphosphorylated TAU protein. Diabetic patients with dysregulated insulin signalling are at increased risk of developing AD. Further, several animal models of diabetes show increased Aβ expression and hyperphosphorylated tau. As we have shown recently, the anti-diabetic drug metfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…Metformin has also been shown to decrease intestinal absorption of glucose [15, 16]. Studies on metformin’s effects in the central nervous system are limited and predominantly consist of in vitro studies, some of which show support for metformin as a neuroprotective agent [17], increasing hippocampal neurogenesis and enhancing cognitive function [18] however, other studies have shown evidence that metformin may increase risk of developing Alzheimer’s disease [19] and be deleterious to neuronal survival acting through its AMPK activating mechanism [20]. Most of these studies utilize a paradigm of short-term metformin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin has also been shown to decrease intestinal absorption of glucose [15, 16]. Studies on metformin’s effects in the central nervous system are limited and predominantly consist of in vitro studies, some of which show support for metformin as a neuroprotective agent [17], increasing hippocampal neurogenesis and enhancing cognitive function [18] however, other studies have shown evidence that metformin may increase risk of developing Alzheimer’s disease [19] and be deleterious to neuronal survival acting through its AMPK activating mechanism [20]. Most of these studies utilize a paradigm of short-term metformin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…MFM also ameliorates AD-like molecular and neuropathological hallmarks of insulin signaling in neuronal insulin resistance in the Neuro-2a cell line (Gupta et al, 2011). In addition, MFM reduces BACE1 and, as a consequence, Aβ production in SH-SY5Y-APP neuroblastoma cells, mouse primary cortical neurons, and wild-type mice (Hettich et al, 2014). Clinical studies reported conflicting results showing a reduced rate of onset of cognitive impairment (Dominguez et al, 2012) as well as a higher risk of developing AD (Imfeld et al, 2012).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…It is considered to be an insulin-sensitizing drug that can inhibit the production of hepatic glucose and increase peripheral glucose uptake. Apart from diabetes, metformin also possesses positive effects on cardiovascular disease and nerve regeneration (Hettich et al 2014;Fung et al 2015). In recent years, the effects of metformin on bone metabolism have received considerable attention; there is a close relationship between glucose and bone metabolism (Meier et al 2016;Starup-Linde and Vestergaard 2016).…”
Section: Introductionmentioning
confidence: 99%